The Role of Omni-channel Integration in driving Customer Satisfaction and Loyalty in Indonesia E-commerce - Fernando, Antonius; Siagian, Sandra Louis; Muthia, Tsabita Indah; Setiowati, Rini (Dinasti International Journal of Education Management and Social Science, 2025)
The rapid growth in consumer expectations and the increasing demand for online shopping have necessitated the integration of distribution systems that can serve customers seamlessly across multiple channels. Despite its potential, implementing an effective omni-channel system presents various challenges, particularly in aligning operations with the values perceived by customers. Addressing this issue, the present study—titled “The Role of Omni-channel Integration in Driving Customer Satisfaction and Loyalty in Indonesia E-commerce”—seeks to contribute to the expanding literature on omni-channel strategies. Specifically, the study aims to empirically examine the relationships between omni-channel order fulfillment integration, integration quality, perceived omni-channel value, customer satisfaction, and customer loyalty. The data analysis uses the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS) to explore these relationships. The findings indicate a positive relationship between omni-channel integration and customer satisfaction, while the quality of omni-channel integration is also positively associated with customer loyalty.